PENGARUH LKS BERBASIS SAINS TEKNOLOGI MASYARAKAT TERHADAP KOMPETENSI SISWA DALAM PEMBELAJARAN IPA FISIKA DI KELAS VIII SMPN 1 KUBUNG KABUPATEN SOLOK - Urai Asmirani (PILLAR OF PHYSICS EDUCATION, 2013)
Objective of this research was to determine the effect of the use of worksheets based science technology society (STS) toward students competence at grade VIII in SMPN 1 Kubung. Type of research is quasi-experimental is the randomized control groups only design. As population in research was all students grade VIII in SMPN 1 Kubung in academic year 2011/2012. There were two instrumens to collect the data, those are written test for cognitive domain, observation sheet for affective domain and scoring rubric for psychomotor domains. The data analysis techniques in this research uses compare means test standard of quality 0,05 for cognitive domain and affective domain. Based on the data analysis it can be concluded that the use of worksheets based STS in physics learning significant effeck to word competence of students in SMPN 1 kubung Kabupaten Solok.   Keywords: teaching materials, worksheets, and  science community technolog